Optimal Solvents for Interfacial Solution Engineering of Perovskite Solar Cells. Issue 9 (15th July 2022) - Heo, Do Yeon; Jang, Won Jin; Jeong, Min Ju; Noh, Jun Hong; Kim, Soo Young
Abstract : Interfacial engineering is extensively used to reduce the interfacial loss caused by surface recombination, improve the crystallinity of the active absorption layer, and enhance the long‐term stability of perovskite solar cells (PSCs). Solution processing techniques, such as spin coating and dip coating, are commonly used to deposit the interfacial layer because of their cost‐effectiveness and simplicity. Although determining suitable solutes for use in these processes is important, selecting appropriate solvents is also crucial. Herein, commonly used solvents are investigated to determine optimal solvents for solution processing by categorizing them into nonpolar and polar groups. The results suggest that the efficiency of the PSCs can be increased by simple solvent treatment. In particular, the efficiencies of systems subjected to hexane (nonpolar) and ethanol (polar) treatment are significantly improved (17.31% and 17.44%, respectively) compared with that of a control device (16.24%). Herein, the effects of pure solvents on the SnO2 –perovskite interface are confirmed and an important direction for investigations that adopt solution processing to improve the efficiency of PSCs, such as research on interlayers and self‐assembled monolayers, is suggested. Abstract : Solvent engineering is a new paradigm for improving the efficiency and stability of perovskite solar cells (PSCs). The incorporation of a pure‐solvent interlayer between the SnO2 electron transport layer and perovskite can increase the PSC efficiency, as an effective strategy for interfacial engineering of PSCs.